A queer mother for the nation : the state and Gabriela Mistral - Fiol-Matta, Licia (University of Minnesota Press, 2002)
A Queer Mother for the Nation weaves a nuanced understanding of how Gabriela Mistral (1889-1957), the first Latin American to win the Nobel Prize for Literature, cooperated with authority and fashioned herself as the figure of Motherhood in collaboration with the state.